SPEECH STYLE USED BY NAJWA SIHAB IN MATA NAJWA TELEVISION TALK SHOW “DI BALIK DIAM BUDIONO” EPISODE - SARI, SYLVIA RATNA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: speech style, types of speech style, Mata Najwa, Najwa Sihab. When communicating, each person may apply different styles of speaking. In Sociolinguistics, different style in speaking is known as speech styles. This study investigates speech style produced by Najwa Sihab in Mata Najwa Metro TV talk show. Mata Najwa is one of Metro TV talk show programs hosted by a senior journalist, Najwa Shihab. In conducting the research, the writer tries to find the speech style used by Najwa Sihab in terms of diction and sentence structure. Moreover, the writer also tries to find out the possible reasons underlying the use of certain style. The main theory used in this study is by Keraf (2008), supported by Kridalaksana (1992), Holmes (2001) and Rais (2012). This study uses qualitative approach since the writer tries to analyze the transcript of Najwa Sihab utterances. The data of the study are Najwa Sihab’s declarative utterances containing speech style in “Di Balik Diam Budiono” episode.The writer finds that Najwa Sihab uses informal style more dominantly than formal style in terms of diction. It means that Najwa tries to be more casual and makes the guest star more comfortable for being interviewed. While in terms of sentence structure, the writer cannot find the parallelism style and the mostly uses by Najwa is repetition style. Repetition is used to emphasize the certain point and also used to affirm something more clearly. From all the styles that are found, the writer interprets the reasons of each style and finds that the types of speech in terms of diction are mostly influenced by the factors of choosing speech style proposed by Holmes (2001), while the reason of choosing speech style in terms of sentence structure are mostly influenced by the function of the speech style itself.Finally, the writer hopes that this study can add knowledge for the students of English Study Program as the reference in conducting further studies of speech style. Moreover, there will be other studies that discuss about speech style with the different object or even the different theory.